Development of acaricide resistance in Pacific spider mite (Tetranychus pacificus) from California vineyards - Stavrinides, Menelaos; Van Nieuwenhuyse, Pieter; Van Leeuwen, Thomas; Mills, Nicholas J. (My University, 2010)
In recent years, grape growers in California reported failures of acaricides against Tetranychus pacificus McGregor. We collected T. pacificus populations from four vineyards and tested them for resistance to bifenazate, propargite and pyridaben. In addition, we sequenced part of the cytochrome b gene of bifenazate-resistant and -susceptible T. pacificus to test for the presence of mutations reported to confer resistance to the congeneric T. urticae. None of the mutations conferring resistance to bifenazate in T. urticae were present in resistant T. pacificus. Resistance levels ranged from full susceptibility to statistically significant 11-fold resistance to pyridaben, sevenfold resistance to bifenazate and fourfold resistance to propargite compared to a susceptible population. Despite the relatively low levels of resistance detected, we estimated that under the conditions of our study the highest field rates of bifenazate and pyridaben application would cause less than 58 and 66% mortality of adult females in the most resistant populations, respectively. In contrast, field rates of propargite application would cause close to 100% mortality in the least susceptible population. These results highlight a potential link between resistance development and reduced field effectiveness for bifenazate and pyridaben. Finally, T. pacificus may be more tolerant to bifenazate and propargite than T. urticae, since the LC(50) values for the susceptible population of T. pacificus were several times higher than LC(50)'s reported for susceptible T. urticae.
Keywords: Bifenazate; Cytochrome b; Propargite; Pyridaben; Resistance; Tetranychus pacificus